Gulf Fritillary Butterfly, Agraulis vanillae (Linnaeus) (Insecta: Lepidoptera: Nymphalidae) - Jaret C. Daniels (EDIS)
EENY-423, a 3-page illustrated fact sheet by Jaret C. Daniels, is part of the Featured Creatures collection. It describes this brightly colored butterfly common across the extreme southern United States — its distribution, description, life cycle and hosts. Includes selected references. Published by the UF Department of Entomology and Nematology, February 2009.